2006
DOI: 10.1186/1465-9921-7-66
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-4 mediates cigarette smoke-induced cytokine production by human macrophages

Abstract: Background: The major risk factor for the development of COPD is cigarette smoking. Smoking causes activation of resident cells and the recruitment of inflammatory cells into the lungs, which leads to release of pro-inflammatory cytokines, chemotactic factors, oxygen radicals and proteases. In the present study evidence is found for a new cellular mechanism that refers to a link between smoking and inflammation in lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 46 publications
7
103
1
1
Order By: Relevance
“…64 It has been recently shown that neutralization of TLR4 with anti-human TLR4 antibody significantly blocked CSE-mediated proinflammatory mediator release by human macrophages. 48 Furthermore, NF-B activation induced by CSE was also attenuated in human macrophages pretreated with anti-human TLR4 antibody. 48 Moreover, subacute (5 weeks) and chronic (26 weeks) CS exposure resulted in increased pulmonary expression of TLR4 in WT mice, and targeted disruption of TLR4 protected against acute and chronic CS-induced lung inflammatory response.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…64 It has been recently shown that neutralization of TLR4 with anti-human TLR4 antibody significantly blocked CSE-mediated proinflammatory mediator release by human macrophages. 48 Furthermore, NF-B activation induced by CSE was also attenuated in human macrophages pretreated with anti-human TLR4 antibody. 48 Moreover, subacute (5 weeks) and chronic (26 weeks) CS exposure resulted in increased pulmonary expression of TLR4 in WT mice, and targeted disruption of TLR4 protected against acute and chronic CS-induced lung inflammatory response.…”
Section: Discussionmentioning
confidence: 90%
“…48 Furthermore, NF-B activation induced by CSE was also attenuated in human macrophages pretreated with anti-human TLR4 antibody. 48 Moreover, subacute (5 weeks) and chronic (26 weeks) CS exposure resulted in increased pulmonary expression of TLR4 in WT mice, and targeted disruption of TLR4 protected against acute and chronic CS-induced lung inflammatory response. 47,65 Therefore, the TLR4-NF-B signal pathway plays an important role in CS-mediated lung inflammatory response.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…19) Furthermore, it was also reported that smokers have increased levels of several inflammatory biomarkers. 20,21) It is thus quite probable that smoking induces inflammation, an atherogenic lipid profile, and a propensity to thrombosis, thereby promoting the development of coronary atherothrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is an important etiologic factor linked to the development of many diseases such as pulmonary, cardio and cerebrovascular diseases, cancers, asthma, chronic obstructive pulmonary disease (COPD) and several others JINQIANG HU, TAO WEI, SIWEN SUN, AIJING ZHAO and CHUNPING XU (Karimi et al 2006). Cigarette smoke is a complex mixture of over 4700 identified constituents that include numerous reactive substances such as a large quantity of reactive aldehydes, free radical species and diverse metals (Hecht 2006).…”
Section: Introductionmentioning
confidence: 99%